Cyclic citrullinated MBP87–99 peptide stimulates T cell responses: Implications in triggering disease. Issue 2 (15th January 2017) - Apostolopoulos, Vasso; Deraos, George; Matsoukas, Minos-Timotheos; Day, Stephanie; Stojanovska, Lily; Tselios, Theodore; Androutsou, Maria-Eleni; Matsoukas, John
Graphical abstract: Abstract: Amino acid mutations to agonist peptide epitopes of myelin proteins have been used to modulate immune responses and experimental autoimmune encephalomyelitis (EAE, animal model of multiple sclerosis). Such amino acid alteration are termed, altered peptide ligands (APL). We have shown that the agonist myelin basic protein (MBP) 87–99 epitope (MBP87–99 ) with crucial T cell receptor (TCR) substitutions at positions 91 and 96 (K 91, P 96 (TCR contact residues) to R 91, A 96 ; [R 91, A 96 ]MBP87–99 ) results in altered T cell responses and inhibits EAE symptoms. In this study, the role of citrullination of arginines in [R 91, A 96 ]MBP87–99 peptide analog was determined using in vivo experiments in combination with computational studies. The immunogenicity of linear [Cit 91, A 96, Cit 97 ]MBP87–99 and its cyclic analog – cyclo(87–99)[Cit 91, A 96, Cit 97 ]MBP87–99 when conjugated to the carrier mannan (polysaccharide) were studied in SJL/J mice. It was found that mannosylated cyclo(87–99)[Cit 91, A 96, Cit 97 ]MBP87–99 peptide induced strong T cell proliferative responses and IFN-gamma cytokine secretion compared with the linear one. Moreover, the interaction of linear and cyclic peptide analogs with the major histocompatibility complex (MHC II, H2-IA s ) and TCR was analyzed using molecular dynamics simulations at the receptor level, in order to gain a better understanding of the molecular recognition mechanisms that underly the different immunological profiles of citrullinated peptides compared to its agonist native counterpart MBP87–99 epitope. The results demonstrate that the citrullination of arginine in combination with the backbone conformation of mutated linear and cyclic analogs are significant elements for the immune response triggering the induction of pro-inflammatory cytokines.